DIFFERENTIAL DIAGNOSTICS OF ELECTROCARDIOGRAM CHANGES IN ISCHEMIC HEART DISEASE AND SPORTS STRESS INFLUENCES - V. I. Pavlov (Кардиоваскулярная терапия и профилактика)
Usual practice of a physician quite oftenly shows difficulties in differentiation of ischemic heart disease and so called “stressor” myocardium changes, occuring in persons participating in sports.